Physiological and morphological responses of Pinus ponderosa seedlings to moisture limitations in the nursery and their implications for restoration - Pinto, Jeremiah R.; Sloan, Joshua L.; Ervan, Gokhan; Burney, Owen T. (Frontiers in Plant Science, 2023)
Successful establishment of Pinus ponderosa seedlings in the southwestern United States is often limited by stressful and harsh site conditions related to drought severity and severe disturbances such as wildfire and mining operations. Seedling quality has an important influence on outplanting performance, but nursery practices that typically employ optimal growing environments may also be limiting seedling morphological and physiological performance on stressful outplanting sites. To address this, a study was established to test alterations in seedling characteristics subjected to irrigation limitations during nursery culture and their subsequent outplanting performance. This study was conducted as two separate experiments: (1) a nursery conditioning experiment examined seedling development of three New Mexico seed sources exposed to three irrigation levels (low, moderate, and high); (2) a simulated outplanting experiment examined a subset of the seedlings from experiment 1 in a controlled outplanting environment consisting of two soil moisture conditions (mesic, maintained via irrigation and dry, irrigated only once). In the nursery study, the lack of interactions between seed source and irrigation main effects for most response variables indicate that low irrigation treatment level responses were consistent across a range of sources. Irrigation treatment levels from the nursery resulted in few morphological differences; however, the low irrigation level increased physiological parameters such as net photosynthetic rate and water use efficiency. In the simulated outplanting experiment, seedlings subjected to less irrigation in the nursery had greater mean height, diameter, needle dry mass, and stem dry mass; additionally, low irrigation levels in the nursery increased the amount of hydraulically active xylem and xylem flow velocity. Overall, this study shows that nursery culture irrigation limitations, regardless of the seed sources tested, can improve seedling morphology and physiological functioning under simulated dry outplanting conditions. This may ultimately translate to increased survival and growth performance on harsh outplanting sites.